Revitalization Of Balango: Local Ceramic Art and Products from Galogandang Luhak Nan Tuo, West Sumatra - Prastawa, Wisnu; Kasman, Selvi; Prihatin, Purwo; Sriyanto, Sriyanto (Institut Seni Indonesia Padang Panjang, 2024)
Balango, a traditional pottery used as a cooking utensil in Minangkabau villages, has been transformed as an interior aesthetic support or aesthetic element, so that balango becomes more dynamic and has prospects as an art commodity. This research aims to examine the revitalization of pottery at Galogandang Pottery Hall in Luhan Nan Tuo, West Sumatra. This research uses a mixed method as a reference strategy for developing the potential of clay for the application of local pottery crafts in a sustainable manner through a creative approach supported by laboratory tests. Balango at Galogandang Pottery Hall, there is a development of local art product designs in the form of flower vases; pendil teapots, and kadhai whose clay raw materials are formulated from three types of soil with a clay fraction of 23% (sandy loam clay); kaolinite (21%), illite (41%), and quartz (38) minerals; oxide composition dominated by SiO2 (37%) and Fe2O3 (35%); burn shrinkage (19%); specific gravity (1.75 g cm-3), porosity (26.60%) and compressive strength (225.48 kg cm-2). This composition can be used to customize new ideas for other products by combining different forms (figurative and abstract), resulting in visually beautiful and functional utilitarian pottery for interiors with artistic quality and local flavor.